Woke Gaming: Digital Challenges to Social Injustice - Gray, Kishonna L.; Leonard, David J. (University of Washington Press, 2018)
From #Gamergate to the daily experiences of marginalization among gamers, gaming is entangled with mainstream cultures of systematic exploitation and oppression. Whether visible in the persistent color line that shapes the production, dissemination, and legitimization of dominant stereotypes within the industry itself, or in the dehumanizing representations often found within game spaces, many video games perpetuate injustice and mirror the inequities and violence that permeate society as a whole. Drawing from the latest research and from popular games such as World of warcraft and Tomb raider, Woke gaming examines resistance to spaces of violence, discrimination, and microaggressions in gaming culture. The contributors of these essays identify strategies to detox gaming culture and orient players toward progressive ends, illustrating the power and potential of video games to become catalysts for social justice
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Beyond Hate: White Power and Popular Culture - King, C. Richard; Leonard, David J. (Cultural politics of media and popular culture, 2016)
Beyond Hate offers a critical ethnography of the virtual communities established and discursive networks activated through the online engagements of white separatists, white nationalists, and white supremacists with various popular cultural texts, including movies, music, television, sport, video games, and kitsch. Outlining the ways in which advocates of white power interpret popular cultural forms, and probing the emergent spaces of white power popular culture, it examines the paradoxical relationship that advocates of white supremacy have with popular culture, as they finding it to be an irresistible and repugnant reflection of social decay rooted in multiculturalism. Drawing on a range of new media sources, including websites, chat rooms, blogs and forums, this book explores the concerns expressed by advocates of white power, with regard to racial hierarchy and social order, the crisis of traditional American values, the perpetuation of liberal, feminist, elitist ideas, the degradation of the family and the fetishization of black men. What emerges is an understanding of the instruments of power in white supremacist discourses, in which a series of connections are drawn between popular culture, multiculturalism, sexual politics and state functions, all of which are seen to be working against white men. A richly illustrated study of the intersections of white power and popular culture in the contemporary U.S., and the use of use cyberspace by white supremacists as an imagined site of resistance, Beyond Hate will appeal to scholars of sociology and cultural studies with interests in race and ethnicity, popular culture and the discourses of the extreme right.
Keywords: 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Télé